Teacher pay, class size and local governments: Evidence from the Latvian reform - Mihails Hazans (Institute for the Study of Labor (IZA), 2010)
This paper employs a rich collection of survey and administrative datasets, including linked school-teacher payroll data, to document the reform of teacher compensation and school network implemented in Latvia amidst the economic crisis of 2008-2010, immediately after territorial reform. We explore diverse responses by local governments in terms of proportion of state subsidy transferred to schools, extent of redistribution of state funds between schools, degree of autonomy in compensation policies given to schools, and municipal contribution to school wage bills. Other things equal, municipalities tend to redistribute funds from schools with high student-teacher ratio (S/T) to ones with low S/T. Nevertheless, the reform has changed the effect of the local student-teacher ratio on teacher earnings per workload from negative to positive of the same size. Survived schools feature strong heterogeneity in terms of workload and staff reduction, change in class size, and compensation strategies. We provide evidence for a substantial incidence of using performance-related criteria for teacher base salary differentiation. We analyze school and individual level determinants of teacher pay using mixed models with municipality and school level random effects.
Keywords: H75; I22; I28; J31; J33; J45; M52; C23; 330; teacher compensation; local governments; linked employee-employer data; Bildungsreform; Lehrkräfte; Besoldung; Kommunalpolitik; Öffentliche Bildungsausgaben; Klassengröße; Lettland